Purification and characterization of bacterial aryl alcohol oxidase from sphingobacterium sp ATM and Its uses in textile dye decolorization - Tamboli, Dhawal P.; Telke, Amar A.; Dawkar, Vishal V.; Jadhav, Shekhar B.; Govindwar, Sanjay P. (Biotechnology and Bioprocess Engineering, 2011)
Aryl alcohol oxidase (AAO) produced by dye decolorizing bacteria Sphingobacterium sp. ATM, was purified 22.63 fold to a specific activity of 21.75 mu mol/min/mg protein using anion exchange and size exclusion chromatography. The molecular weight of the purified AAO was found to be 71 kDa using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and confirmed by zymography of AAO using L-dopa. The enzyme showed substrate specificity towards veratryl alcohol, followed by n-propanol. The optimum pH and temperature of purified AAO were found to be 3.0 and 40 degrees C, respectively. The K(m) and V(max) of AAO was 1.1615 mM and 3.13 mM/min when veratryl alcohol was used as substrate. Sodium azide showed maximum inhibition while ethylenediamine tetra acetic acid (EDTA), L-cysteine and dithiothreitol showed slight inhibition. Metal ions also showed slight inhibition. HPLC analysis confirmed the degradation of Direct Red 5B. The metabolite obtained after decolorization of Direct Red 5B was characterized as 3 diazenyl 7 [-(phenyl carbonyl) amino] naphthalene-2-sulfonic acid using GC-MS analysis.
Keywords: aryl alcohol oxidase; Direct Red 5B; dye decolorization; ion exchange chromatography; Sphingobacterium sp ATM